The Representation of Health Literacy Level in Millennial Adolescents Healthy Living Behaviour - Indira Irawati; Laksmi Laksmi (Buletin Al-Turas, 2021)
The purpose of this study was to identify the level of health literacy among millennial adolescents in Indonesia based on gender, education level, and economic status, and their representation in healthy living behaviors. This research used a quantitative approach with a case study analysis method. Respondents are teenagers from 15-18 years old at high school. The questionnaire was distributed to 655 samples, in February-March 2021. The result showed that millennial adolescents had a habit of looking for health information, especially through electronic media. They explored the disease and medication when there were relatives who get ill. They communicated with medical workers and were likely to be interested in modern health information. They were able to analyze and critique health information although it was a simple one. Adolescents did not manage health information systematically because they did not study it deeper. The millennial adolescents had a literacy rate of functional, interactive, and critical in the good categories, but the value of the coefficient of critical literacy levels was low. The factors that influenced this level were a robust economy, excellent education, and female gender identity. The representation of the level of literacy was manifested in an understanding of disease, medication, and healthy lifestyles, simply limited to their needs as adolescents. The suggestion was the need to increase health information maximally; as well as role models for managing health information so that adolescents could implement health practices independently